The Effects of Cooperative Learning on Students’ Mathematics Achievement, Mathematics Self-Efficacy and Mathematics Anxiety in High School Mathematics (Journal of Informatics and Mathematical Sciences, 2021)
The purpose of this study is to identify the effects of cooperative learning on students’ mathematics achievement, mathematics self-efficacy and mathematics anxiety. This study employed a quasi-experimental design with pre-test and post-test. For this purpose, 112 students in 10th grade participated in our study to compare the cooperative learning method with traditional direct instruction method. These students has been selected through a random sampling technique, so that 56 students taught through cooperative learning, formed two experimental groups (girls group and boys group), and 56 students taught through traditional direct instruction, formed two control groups. Sample of the students were also equated on the basis of socio-economic status and achievement in the mathematics. Data were analyzed using ANOVA and ANCOVA to test hypotheses at 0.05 significance level. The results of this comparison show that cooperative learning has positive effects on students’ mathematics achievement, improves the mathematics self-efficacy of students and reduces students’ mathematics anxiety. In addition, the results of post-hoc pairwise comparisons show that cooperative learning has similar effects on mentioned variables for boy and girl students in experimental groups.
Keywords: Cooperative learning; Traditional direct instruction; Mathematics achievement; Mathematics anxiety; Mathematics self-efficacy